1974
DOI: 10.2172/4186006
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic studies of Gable Mountain Pond

Abstract: This publication represents a summary report on the aquatic studies a t Gable Mountain Pond from [1972][1973][1974] Native goldfish had maximum and average 1 3 7~s concentrations of about 340 and 170 pCi/g dry w t , respectively. Algae, macrophytes, and d e t r i t u s comprised the main food items of the goldfish, and the 1 3 7~s levels in the plants were usually higher than the 1 3 7~s concentration in the f i s h . Uncontaminated goldfish r e s t r i c t e d t o areas of relatively high and low levels of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Sorptiondesorption is probably the primary control for %Sr and 137Cs migration at the 216-A-25 Gable Mountain Pond. Cushing and Watson (1974) noted that I3?Cs appears to be strongly held in the sediments immediately below the pond. The same is not expected for ' %r; it is thought to occur at the top of the aquifer (Serkowski and Jordan 1989).…”
Section: Contaminant Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…Sorptiondesorption is probably the primary control for %Sr and 137Cs migration at the 216-A-25 Gable Mountain Pond. Cushing and Watson (1974) noted that I3?Cs appears to be strongly held in the sediments immediately below the pond. The same is not expected for ' %r; it is thought to occur at the top of the aquifer (Serkowski and Jordan 1989).…”
Section: Contaminant Sourcementioning
confidence: 99%
“…In 1971 and 1972, PNNL personnel conducted a study of Gable Mountain Pond (Cushing and Watson 1974). Cushing and Watson (1974) found that 137Cs accounted for 90% of the radioactivity at the pond, and 90% of 137Cs occurred in the top 5 cm (2 in.)…”
Section: Lo6 Ft*) Thementioning
confidence: 99%
See 2 more Smart Citations
“…Cushing and Watson (1974) analyzed radionuclides in sediment samples collected from the bottom of the pond with sediment coring tubes and Ekman dredges. The maximum concentrations measured for plutonium and americium were 1.5 pCi/g plutonium-239/240, less than 0.08 pCi/g plutonium-238, and 1.4 pCi/g americium-241.…”
Section: Waste Site 216-a-25mentioning
confidence: 99%